Difference in physiological responses to sound stimulation in subjects with and without fear of dental treatments - Zakir, H.M. (Springer Verlag (Germany), 2008)
The effects of sound generated by an ultrasonic dental scaler and a dental turbine on heart rate, systolic and diastolic blood pressure, and hemodynamic changes in the frontal cortex were measured and compared with those of pure tone stimulation in 17 young volunteers. Near-infrared spectroscopy and the Finapres technique were used to measure hemodynamic and cardiovascular responses, respectively. The dental sound changed the various physiological parameters. To determine if this change was related to participants’ previous experiences with dental treatment, participants were divided into two groups: those who had a previous unpleasant experience with dental treatment and those who had not. Participants with previous unpleasant dental experiences showed a signifi cant decrease in cerebral blood fl ow. Participants who had not had an unpleasant dental experience did not show signifi cant changes in cerebral blood fl ow. Thus, although sounds associated with dental treatment may reduce cerebral blood fl ow, this effect may depend on the dental experiences of the patient. It is recommended that dentists treat patients gently and with empathy to promote a friendly image of dentistry.